Otwarcie filmu fabularnego, jego funkcje i znaczenie - Jaroszuk, Grzegorz (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
Legendary American producers who’d accepted to read tens of scripts had a justified approach to read only first ten pages. Although on a first sight it may appear negligence, they knew well that if they are not convinced by the first pages of the script, it is very likely that the audience won’t feel convinced either. The article concerns the role of the film opening and its structure. Its functions and transformations are described upon the examples of films by Ingmar Bergman and Paul Thomas Anderson.